The Innovative Strategies of Arabic Language Education Lecturers in the Era of Digital Disruption for Student Character Formation - Nurfadhila, Ulfah; Sofiyyahs, Siti (Shaut al Arabiyyah, 2025)
This study aims to identify and analyze innovative strategies in Arabic Language Education (PBA) learning at the university level in the era of digital disruption. The research employed a library research method by reviewing relevant scientific articles published between 2023 and 2025. The findings reveal five major categories of innovative strategies: (1) the use of interactive visual media, (2) gamification in learning, (3) project-based learning and role-play, (4) the utilization of adaptive Learning Management Systems (LMS) powered by artificial intelligence (AI), and (5) the integration of mobile learning and Islamic applications. These strategies have been proven to enhance student engagement, motivation, and comprehension of PBA content. However, their implementation faces challenges such as limited infrastructure, lecturers’ digital literacy, and potential technological distractions. This study recommends collaboration among educators, educational technology developers, and university policymakers to create relevant, effective, and value-based PBA learning. Keywords: Arabic Languange Education, innovative strategies, digital disruption era, gamification